An Intertemporal Model of Rational Criminal Choice - Jenny Williams
This research presents a dynamic model of crime in which agents anticipate future consequences of their actions. Current period decisions affect future outcomes by a process of capital accumulation. While investigating the role of human capital, the focus of our study is on a form of capital that has received somewhat less attention in the literature, social capital. Social capital is an index of one's 'stock' in society. Introduction of social capital into the utility function results in an intertemporally nonseparable preference structure which admits state dependence in the decision to participate in crime. Our model is empirically implemented using panel data on a sample from the 1958 Philadelphia Birth Cohort Study. In estimation, we take account of unobserved choices in states not realized, which potentially depend on individual specific heterogeneity, by using simulation techniques. Our results provide evidence of state dependence in the decision to participate in crime. We also find that the initial level of social capital stock is important in determining the pattern of criminal involvement in adulthood.